1985
DOI: 10.1677/joe.0.1040407
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 5-hydroxytryptamine uptake blockers on the concentration in brain of 5-hydroxytryptamine and 5-hydroxyindoleacetic acid in male rats, pro-oestrous rats and ovariectomized rats treated with oestrogen and progesterone

Abstract: The aim of this study was to determine the effect of 5-hydroxytryptamine (5-HT) uptake blockade on 5-HT turnover by measuring the concentrations of 5-HT and 5-hydroxyindoleacetic acid (5-HIAA) in brain with the aid of high performance liquid chromatography and electrochemical detection. The indoleamines were measured in the anterior hypothalamus (AH), posterior hypothalamus (PH) and raphe nuclei 30 min after the i.v. injection of either alaproclate (30 mg/kg) or zimelidine (20 mg/kg). The effect of alaproclate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1985
1985
1987
1987

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This was unexpected as zimelidine, and particularly its active metabolite norzimelidine, has been found to be a more potent inhibitor of 5-HT uptake in vitro than alaproclate (Fuxe et al 1977). However, there are indications that the potency of alaproclate may have been underestimated, since it has been shown to be more potent than zimelidine in behavioural studies (Fuxe et al 1977), and Horn & Watts (1985) found that under similar conditions to those used in the present paper, alaproclate, but not zimelidine, affected the 5-HIAA/5-HT ratio in the raphe nucleus of model 2. More recently, it has been reported that zimelidine has no effect on endocrine function in man (Syvalahti, Nagy & Van Praag, 1979;Kletzky, St Michel, Mashchak & Coleman, 1983).…”
Section: Discussionmentioning
confidence: 51%
“…This was unexpected as zimelidine, and particularly its active metabolite norzimelidine, has been found to be a more potent inhibitor of 5-HT uptake in vitro than alaproclate (Fuxe et al 1977). However, there are indications that the potency of alaproclate may have been underestimated, since it has been shown to be more potent than zimelidine in behavioural studies (Fuxe et al 1977), and Horn & Watts (1985) found that under similar conditions to those used in the present paper, alaproclate, but not zimelidine, affected the 5-HIAA/5-HT ratio in the raphe nucleus of model 2. More recently, it has been reported that zimelidine has no effect on endocrine function in man (Syvalahti, Nagy & Van Praag, 1979;Kletzky, St Michel, Mashchak & Coleman, 1983).…”
Section: Discussionmentioning
confidence: 51%
“…This effect of pCPA, however, was not confirmed by Horn & Watts (1985). We have shown that restoration of serotonin synthesis by 5-hydroxytryptophan, which does not reverse the inhibitory action of pCPA on dopamine synthesis (Coen et al 1983), depressed pro¬ lactin release.…”
Section: Discussionmentioning
confidence: 73%
“…These results demonstrate that 5-HT stimulates gonadotrophin release by acting directly on LHRH terminals in the median eminence from pro-oestrous INTRODUCTION A physiological role for serotonin (5-HT) in the regulation of gonadotrophin secretion has frequently been suggested (Weiner & Ganong, 1978;Coen & MacKinnon, 1979;Biegon, Bercovitz & Samuel, 1980;Marko & Flückiger, 1980;Walker, 1980Walker, , 1983Horn & Fink, 1985;Horn & Watts, 1985), but has not yet been definitively established.…”
mentioning
confidence: 99%